The association between coronary microvascular dysfunction and carotid intima media thickness in patients with cardiac syndrome X. (1st July 2016) - Sucato, Vincenzo; Evola, Salvatore; Novo, Giuseppina; Corrado, Egle; Coppola, Giuseppe; Andolina, Giuseppe; Assennato, Pasquale; Novo, Salvatore
Abstract: Objective: The aim of this study was to evaluate in patients with cardiac syndrome X (CSX), using validated angiography indices, coronary blood flow and myocardial perfusion of the microcirculation to assess whether there is greater microvascular dysfunction in patients with increase of carotid intima media thickness (C-IMT), compared to those who do not have. Methods: Our study was performed on a population 124 patients with CSX that underwent coronary angiography and carotid ultrasound. We divided the sample into two categories: patients with increase of C-IMT and those without increase. We calculated Gibson and Yusuf indices for each patient based on angiographic images, including TIMI Frame Count (TFC), Myocardial Blush Grade (MBG) and Total Myocardial Blush Score (TMBS). Results: Our sample compared two groups: patients with increase of C-IMT (n-63) and patients without increase of C-IMT (n-61). We showed that patients with increase C-IMT had a longest TFC of three major coronary arteries (TFC LAD 44.7 ± 12.5; TFC RCA 26.2 ± 6.9; TFC CX 27 ± 5.9), than control group. We found lower MBG on three coronary arteries (MBG LAD 2.5 ± 0.3; MBG RCA 2.3 ± 0.3; MBG CX 2.1 ± 0.32) in patients with increase of C-IMT than control group, with good statistical significance. Conclusion: Analysis of microcirculation trough angiography indexes in patients with CSX with increase of C-IMT and without has led to asses that patients with increase of C-IMT population has a greater involvement of microcirculation than patients without.